Comparative analysis of architectural regulations in fire stations in Chile, Colombia, Venezuela and Peru - Vidal-Valladolid, Miguel Ángel; Goluchowska-Trampczynska, Katarzyna (Estoa. Journal of the Faculty of Architecture and Urbanism, 2022)
The ad hoc comparative analysis method, applied to the standards of fire stations in urban areas of South American Andean countries, allowed evaluating similarities and differences between the implicit norms or regulations of Venezuela, Colombia, Chile and Peru, with the purpose of obtaining design criteria or guidelines for new stations in Lima. Among the results obtained, location criteria have been established based on aspects such as: coverage area, location and risks for the building, public services, emergency communication network, among others. The architectural program consists of areas for: equipment and maintenance, training and education, residential and leisure, administrative and services. The architectural design criteria were grouped into: formal, functional aspects, and technical specialties that condition architecture. Additionally, it was concluded that in the urban area of ​​Lima, for the architectural program, a minimum of 1,317.6 m2 of roofed area is required.